2020
DOI: 10.1177/0743558420979123
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Mentoring for Young Adults: A Multi-Method Study

Abstract: Closeness between mentor and mentee is previously defined as an important indicator of relationship quality in youth mentoring, but whether this is the case in instrumental mentoring for young adults remains unclear. This is an exploratory study examining how instrumental mentoring serves young adults in their instrumental needs and how relational closeness develops. We applied a mixed-methods design, using quantitative data from a study of an instrumental mentoring program in Rotterdam, The Netherlands ( N = … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…However, it might reveal younger negotiators’ need to engage in problem-solving (i.e. collaboration), possibly for instrumental reasons (Schenk et al , 2021), when they have sufficient power to do so. Moreover, the creativity by age interaction was significant and showed that negotiators in the high creativity condition were more collaborative the younger they were.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it might reveal younger negotiators’ need to engage in problem-solving (i.e. collaboration), possibly for instrumental reasons (Schenk et al , 2021), when they have sufficient power to do so. Moreover, the creativity by age interaction was significant and showed that negotiators in the high creativity condition were more collaborative the younger they were.…”
Section: Discussionmentioning
confidence: 99%
“…We further found that low-power negotiators reported using more collaboration when in the high creativity condition and younger. This finding might be explained by the instrumental goals of low-power individuals, especially when they are younger (Schenk et al , 2021), which prompts them to make use of any opportunity they are offered to think creatively and find mutually beneficial solutions to conflicts with powerful others.…”
Section: Discussionmentioning
confidence: 99%
“…In many schools, mentors are adults from the community who meet weekly with their assigned young people on school premises (Karcher, 2008), although in Spain it is usually the school's teaching staff. On the part of mentors, it might be useful for them to provide adolescents with support that also contributes to their personal development through goal setting; goal setting that underpins holistic development can give adolescents a sense of control over the issues they face on a daily basis, as well as help to strengthen personal relationships of school mentoring (Schenk et al, 2021). Moreover, given that school-based mentoring is one of a teacher's responsibilities in Spain, it is essential that training programs be organized to improve upon its effectiveness.…”
Section: Relevance To the Practice Of School Psychologymentioning
confidence: 99%
“…Consequently, certain relationships help people meet their “instrumental” needs (i.e. skills and competencies building, career knowledge), while others help them meet their needs to grow personally, self-identify with their tasks and/or organization, or express their aspirations and sense of purpose in relation to their tasks and organization (Kahn, 2007, p. 194; Schenk et al. , 2021, p. 400).…”
Section: Introductionmentioning
confidence: 99%